ASF1B promotes gastric cancer progression by modulating H2AC20 and activating PI3K/AKT and ERK1/2 pathways - Zhao, Mengyuan; Zhang, Junchang; He, Yanjun; You, Chongge (Frontiers in Pharmacology, 2025)
BackgroundGastric cancer (GC) ranks among the most prevalent malignant neoplasms globally and is associated with a significant mortality rate. Despite the availability of various therapeutic interventions for GC, the overall prognosis for this disease remains unfavorable. This can be attributed to several factors, including delayed diagnosis and the inherent heterogeneity of the tumors. With the continuous enrichment of treatment methods, GC has entered an era of comprehensive treatment oriented toward precision and standardization.MethodsThrough the application of bioinformatics and assessments of tissue microarrays, this study has selected the histone chaperone Anti-Silencing Function 1B (ASF1B) for detailed analysis, including clinical specimens. We then constructed ASF1B knockout and overexpression cell lines, and conducted biological function tests on this basis, validated at mouse and organoid levels. Additionally, human immunereconstitution was performed in NOD-PrkdcscidIl2rgem1/Smoc (NSG) mice, followed by flow cytometry analysis of mouse blood. Mechanically, protein-protein interaction analyses were conducted utilizing Immunoprecipitation-Mass Spectrometry (IP-MS) and Tandem mass tagging (TMT) methodologies to identify protein clusters.ResultsThe analysis demonstrated that ASF1B is significantly upregulated in GC tissues and correlates with unfavorable prognostic outcomes. Biological function tests provided that ASF1B contributes to tumor cell proliferation, colony formation, invasion and migration, and plays an important role in the progression of GC in vivo. These findings were validated at both the mouse and organoid levels. Additionally, we observed that ASF1B is involved in the tumor microenvironment, where ASF1B knockdown increases CD8+ T cell infiltration, indicating a negative correlation with immune activation. Mechanically, our investigation revealed that ASF1B emerged as a promoter of GC progression by downregulating H2A clustered histone 20 (H2AC20), thereby influencing the activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) and extracellular regulated protein kinases (ERK)1/2 signaling pathways.ConclusionASF1B, recognized as an oncogene, contributes to the initiation and progression of tumors, positioning it as a prospective target for therapeutic intervention in GC.